2006
DOI: 10.1177/1098214005284974
|View full text |Cite
|
Sign up to set email alerts
|

A Professional Development Unit for Reflecting on Program Evaluator Competencies

Abstract: This article describes an interactive professional development unit that engages both novice and experienced evaluators in (a) learning about the Essential Competencies for Program Evaluators (ECPE), (b) applying the competencies to program evaluation contexts, and (c) using the ECPE to reflect on their own professional practices. The article briefly summarizes current issues about program evaluator competencies and the components of effective professional development. It then describes the ECPE; the objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…Some of the survey questions were adapted and modified from questions in a paper published on the needs assessment of a graduate-level course on optical networking,8 and some were adapted from questions from Ghere et al9 Other questions were added to address needs assessment specific to a DPH master’s program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the survey questions were adapted and modified from questions in a paper published on the needs assessment of a graduate-level course on optical networking,8 and some were adapted from questions from Ghere et al9 Other questions were added to address needs assessment specific to a DPH master’s program.…”
Section: Methodsmentioning
confidence: 99%
“…The third and final part of the questionnaire asked the participants to self-assess their own competency level in DPH. We used a self-assessment rating scale (1–6) that has been validated and used extensively by Ghere et al9 in a “program evaluator competencies self-assessment tool,” as part of professional development sessions, graduate-level seminars, and introductory program evaluation courses that conduct a self assessment. The list of skills and knowledge, as well as the core competencies for DPH were adopted from the competencies given by the AAPHD.…”
Section: Methodsmentioning
confidence: 99%
“…The result indicated that both of the dimensions of competencies are relevant and significant, particularly with the personality traits as being a dominant contributor to their effectiveness More relevant hints can be found from literature. Ghere et al (2006) considered professional competencies for programme evaluators in North America the essential knowledge, skills and dispositions necessary for the evaluators to conduct programme evaluation effectively. They specified programme evaluators' professional competencies are in six major categories including professional practice, systemic inquiry, situational analysis, project management, reflective practice and interpersonal competence.…”
Section: Quality In Higher Educationmentioning
confidence: 99%
“…Stevahn et al affirmed that the field of programme evaluation would benefit from evaluator competencies through improved training, enhanced effective practice, the advancement of research on evaluation and the potential for continued professionalisation of the field. The version of the 'Essential Competencies for Programme Evaluators' originally developed by King and her colleagues in 2001 was later revised into an easily accessible format (Ghere et al, 2006) so called the taxonomy of essential competencies for programme evaluators, which includes 61 items spread throughout six domains: professional practice, systematic inquiry, situational analysis, project management, reflective practice and interpersonal competence (Wilcox, 2012).…”
Section: Understanding Of Professional Competences For External Qualimentioning
confidence: 99%
See 1 more Smart Citation